Diversified amino acid-mediated allosteric regulation of phosphoglycerate dehydrogenase for serine biosynthesis in land plants. Issue 12 (25th June 2021) - Okamura, Eiji; Ohtaka, Kinuka; Nishihama, Ryuichi; Uchida, Kai; Kuwahara, Ayuko; Mochida, Keiichi; Hirai, Masami Yokota
Abstract : The phosphorylated pathway of serine biosynthesis is initiated with 3-phosphoglycerate dehydrogenase (PGDH). The liverwort Marchantia polymorpha possesses an amino acid-sensitive MpPGDH which is inhibited by l -serine and activated by five proteinogenic amino acids, while the eudicot Arabidopsis thaliana has amino acid-sensitive AtPGDH1 and AtPGDH3 as well as amino acid-insensitive AtPGDH2. In this study, we analyzed PGDH isozymes of the representative land plants: the monocot Oryza sativa (OsPGDH1–3), basal angiosperm Amborella trichopoda (AmtriPGDH1–2), and moss Physcomitrium ( Physcomitrella ) patens (PpPGDH1–4). We demonstrated that OsPGDH1, AmtriPGDH1, PpPGDH1, and PpPGDH3 were amino acid-sensitive, whereas OsPGDH2, OsPGDH3, AmtriPGDH2, PpPGDH2, and PpPGDH4 were either sensitive to only some of the six effector amino acids or insensitive to all effectors. This indicates that PGDH sensitivity to effectors has been diversified among isozymes and that the land plant species examined, except for M. polymorpha, possess different isozyme types in terms of regulation. Phylogenetic analysis suggested that the different sensitivities convergently evolved in the bryophyte and angiosperm lineages. Site-directed mutagenesis of AtPGDH1 revealed that Asp 538 and Asn 556 residues in the ACT domain are involved in allosteric regulation by the effectors. These findings provide insight into the evolution of PGDH isozymes, highlighting the functional diversification of allosteric regulation in land plants.